ANALISA EFISIENSI ROOFTOP SOLAR COPRA DRYER DENGAN SUSUNAN KOLEKTOR SECARA SERI - Sulaeman Sulaeman; M. Rusyadi (Jurnal Teknik Mesin (JTM), 2013)
Rooftop solar copra dryer tool is an instrument used for drying copra with capacity ± 40 kg, for one drying. The purpose of this research is to see how to efficiency drying in a series connectivity on copra process of drying. Using the dryer solar can exsiccate drain agricultural products. Where the work plase, sunlight absorbed or strored through solar collectors, heat will come from the collector come into a system of air flow to the piping system and forward to the drying. Design tool dryer aims to exsiccate copra of the water is decreased from 52.68 % until 5-6 %. Medium dryer is the heat produced by the capture of the sun and distributed for ciblyin to the drying chamber they would be used for drying copra. After doing research with the experimental method to directly observe and measure the way things are done in the dryer and then do the processing and evaluation of test data. From the results of tests and calculations, drying wits series to get a final moisture content of the materiall is achieved after 25 hours of drying by using a tool maker Rooftop wits 5.97 %. Final moisture content of the materiall is achieved after 25 hours of drying with direct drying wits 24%. Rooftop solar copra dryer appliance is more Effective and Efficient. Un contaminated by air environment (dust, sand, vermin and its other)